2018
DOI: 10.1039/c8tc02900h
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically structured cellulose aerogels with interconnected MXene networks and their enhanced microwave absorption properties

Abstract: Hierarchically structured cellulose aerogels with interconnected MXene networks have low densities and enhanced microwave absorption performances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
98
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(99 citation statements)
references
References 51 publications
0
98
0
1
Order By: Relevance
“…Freeze casting facilitates the optimized utilization of these effects as it enables the controlled alignment of heterogeneous nanostructures at low volume fractions in porous materials, [ 43c,d,62i,81b,140 ] aligned porous nanocomposites [ 114,141 ] and conductive polymer composites with 3D aligned porous fillers [ 68,119 ] as advanced electromagnetic interference shielding materials. That EMI SE divided by thickness of the aligned porous shielding materials as a function of density is summarized in Figure A.…”
Section: Emerging Applications Of Freeze Cast Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Freeze casting facilitates the optimized utilization of these effects as it enables the controlled alignment of heterogeneous nanostructures at low volume fractions in porous materials, [ 43c,d,62i,81b,140 ] aligned porous nanocomposites [ 114,141 ] and conductive polymer composites with 3D aligned porous fillers [ 68,119 ] as advanced electromagnetic interference shielding materials. That EMI SE divided by thickness of the aligned porous shielding materials as a function of density is summarized in Figure A.…”
Section: Emerging Applications Of Freeze Cast Materialsmentioning
confidence: 99%
“…Finally, it is worth noting that recently 2D MXene‐based aligned porous structures have been emerging as alternative EMI shielding materials due to their electrical conductivity. [ 9c,81,140b ] Koo and co‐workers [ 140b ] recently reported a 3D porous Ti 3 C 2 T x /CNT aerogel fabricated via a bidirectional freezing casting for lightweight EMI shielding application. As illustrated in Figure 22B, the synergism of its high‐conducting and lamellar porous structure contributed extensively to EMI SE value of 103.9 dB at 3 mm thickness at the X‐band frequency.…”
Section: Emerging Applications Of Freeze Cast Materialsmentioning
confidence: 99%
“…The Ti 3 C 2 T x MXenes/carbon‐nanospheres hybrids exhibit an optimal reflection loss of −54.67 dB at 3.97 GHz. Hierarchically structured cellulose aerogels with interconnected MXene (Ti 3 C 2 T x ) network were prepared via freeze‐casting and chemical cross‐linking process by Sui and co‐workers (Figure d) . The cellulose was effectively combined with MXene nanosheets to form the conductive network through the covalent cross‐linking and hydrogen‐bond interaction.…”
Section: Electrochemical Energy Conversion and Storage Applicationsmentioning
confidence: 99%
“…As agraphene-like 2D material, the distinctive properties of MXenes,e specially the high hydrophilicity and metallic conductivity,m ake them attractive for many applications,s uch as energy storage,s ensors,c atalysis,n anocomposites,a nd electromagnetic interference (EMI) shielding. [18,19] Up to now,a pplications of MXenes as building blocks,functional assemblies including one-dimensional (1D) fibers, [20][21][22] 2D films, [23][24][25][26][27] and 3D monoliths [28][29][30][31][32] have been reported through av ariety of assembly strategies.H owever,[*] Prof.…”
mentioning
confidence: 99%
“…As agraphene-like 2D material, the distinctive properties of MXenes,e specially the high hydrophilicity and metallic conductivity,m ake them attractive for many applications,s uch as energy storage,s ensors,c atalysis,n anocomposites,a nd electromagnetic interference (EMI) shielding. [18,19] Up to now,a pplications of MXenes as building blocks,functional assemblies including one-dimensional (1D) fibers, [20][21][22] 2D films, [23][24][25][26][27] and 3D monoliths [28][29][30][31][32] have been reported through av ariety of assembly strategies.H owever, despite such progress,l ittle attention has been paid to the interfacial properties of MXenes between two immiscible liquids (e.g.,oil and water), and the construction of functional assemblies by the interfacial self-assembly of MXenes is still limited. Thei nherent negative charge of the oil-water interface is the primary reason underpinning this.P ristine MXenes are negatively charged and strongly hydrophilic and, as such will not segregate to the interface,b ut remain dispersed in the aqueous phase.V ery recently,bythe electrostatic adsorption of cationic cetyltrimethylammonium bromide (CTAB) onto the MXene surface,H uang and coworkers reported that the hydrophilic-hydrophobic balance of MXene could be tuned, and stable Pickering emulsions could be prepared.…”
mentioning
confidence: 99%